Pengaruh Penggunaan Media Google Form terhadap Peningkatan Hasil Belajar Akidah Akhlak MI Al-Hijrah Bontang Tahun Pelajaran 2023/2024 - Maharani, A. Ayu Saputri (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research is a quantitative research. The source of data was obtained from interviews with deputy principals and teachers of Akidah Akhlak. Observations were carried out in accordance with the needs of the data, in addition to these two sources, the researcher also distributed questionnaires to students as respondents as many as 51. The results of the respondents' data were analyzed using Likert scale analysis. After the test is carried out, it will show the results of the research. The results of the study show that google form media has a significant effect on the improvement of learning outcomes of Moral Beliefs, this can be proven if the tcount value is > from the table, then the test decision is r significant correlation analysis, Ho analysis is rejected and Ha is accepted. Based on the calculation, it can be seen that the tcount > ttable or 5,373 > 2,007, then Ha is accepted. The conclusion shows that there is an influence of the use of google form media on the improvement of learning outcomes of Akidah Akhlak students of MI AL-Hijrah Bontang.